2013
DOI: 10.1016/j.ceramint.2012.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Solution combustion synthesis of α-Al2O3 using urea

Abstract: The processes involved in the solution combustion synthesis of a-Al 2 O 3 using urea as an organic fuel were investigated. The data describing the influence of the relative urea content on the characteristic features of the combustion process, the crystalline structure and the morphology of the aluminium oxide are presented herein. Our data demonstrate that the combustion of stable aluminium nitrate and urea complexes leads to the formation of a-alumina at temperatures of approximately 600-800 1C. Our results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…Various researchers have reported that diaspore (␣-AlOOH) can be decomposed directly to ␣-Al 2 O 3 via no ␥-Al 2 O 3 with annealing at ca. 450 • C [31,32]. Accordingly, the hydrothermal process might have promoted the generation of diaspore-like species in the sol and the following crystallization of the gel to ␣-Al 2 O 3 .…”
Section: Hydrothermal Alumina Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have reported that diaspore (␣-AlOOH) can be decomposed directly to ␣-Al 2 O 3 via no ␥-Al 2 O 3 with annealing at ca. 450 • C [31,32]. Accordingly, the hydrothermal process might have promoted the generation of diaspore-like species in the sol and the following crystallization of the gel to ␣-Al 2 O 3 .…”
Section: Hydrothermal Alumina Gelmentioning
confidence: 99%
“…For all the alumina gels, peaks due to ␥-Al 2 O 3 were detected at ca. [30][31][32][33][34][35][36][37][38][39][40]46, and 67, and no peaks due to ␣-Al 2 O 3 appeared. The ␥-Al 2 O 3 peaks appeared to become sharp with the increase in hydrothermal time.…”
Section: Hydrothermal Alumina Gelmentioning
confidence: 99%
“…Apesar da sua simplicidade em termos de processo, as características estruturais da cerâmica produzida pelo método de síntese por combustão assistida por micro-ondas são dependentes de vários parâmetros que podem influenciar na reação, tais como tipo de combustível, quantidade de água na solução precursora, potência do micro-ondas e razão combustível/oxidante [9][10][11][12][13][14]. No caso da síntese do Al 2 O 3 , vários trabalhos já relataram o uso de diferentes tipos de combustíveis [15][16][17].…”
Section: Introductionunclassified
“…It implies a reduction-oxidation (redox) reaction to give the desired products [16]. The stable phases of Al2O3 were formed when using various combustion agents such as urea [17,18], glycine [19], triethanolamine [7] etc. However, the aforementioned combustion agents are known to give a more violent combustion.…”
Section: Introductionmentioning
confidence: 99%